Statement on Race and Injustice in the United States of America (International bulletin of mission research, 2020)
In light of recent developments in the United States and around the world, impelled by the murder of George Floyd and countless other African-Americans, the leaders of three professional missiological societies jointly announced a statement on race and injustice on June 25, 2020. Thomas J. Hastings, the OMSC executive director and IBMR editor, wholeheartedly endorses the statement.